Meat myths and marketing - Bogueva, Diana; Phau, Ian (2015)
This chapter explores how marketing uses the creation and perpetuation of myths to reinforce demand for meat amongst mainstream consumers. It explores advertising misinformation including with regards the place of meat in our culture, its nutritional value, its association with affluence, masculinity and the benefits of small-scale production. The power of marketing is within the context of whether marketing has a role to play in decreasing rather than perpetuating meat-consumption.